Natural Killer Cell Derived Microvesicles Affect the Function of Trophoblast Cells - Dmitry Sokolov; Alina Gorshkova; Kseniia Markova; Yulia Milyutina; Kseniya Pyatygina; Maria Zementova; Andrey Korenevsky; Valentina Mikhailova; Sergey Selkov (Membranes, 2023)
The interaction of natural killer (NK) and trophoblast cells underlies the formation of immune tolerance in the mother–fetus system and the maintenance of the physiological course of pregnancy. In addition, NK cells affect the function of trophoblast cells, interacting with them via the receptor apparatus and through the production of cytokines. Microvesicles (MVs) derived from NK cells are able to change the function of target cells. However, in the overall pattern of interactions between NK cells and trophoblasts, the possibility that both can transmit signals to each other via MVs has not been taken into account. Therefore, the aim of this study was to assess the effect of NK cell-derived MVs on the phenotype, proliferation, and migration of trophoblast cells and their expression of intracellular messengers. We carried out assays for the detection of content transferred from MV to trophoblasts. We found that NK cell-derived MVs did not affect the expression of CD54, CD105, CD126, CD130, CD181, CD119, and CD120a receptors in trophoblast cells or lead to the appearance of CD45 and CD56 receptors in the trophoblast membrane. Further, the MVs reduced the proliferation but increased the migration of trophoblasts with no changes to their viability. Incubation of trophoblast cells in the presence of MVs resulted in the activation of STAT3 via pSTAT3(Ser727) but not via pSTAT3(Tyr705). The treatment of trophoblasts with MVs did not result in the phosphorylation of STAT1 and ERK1/2. The obtained data indicate that NK cell-derived MVs influence the function of trophoblast cells, which is accompanied by the activation of STAT3 signaling.